PREMEDICATION PROTOCOLS IN DENTAL PRACTICE IN NON-ALLERGIC PATIENTS. - Angelina Kisselova; Adriana Krasteva; Assya Krasteva (Peytchinski Publishing, 2011)
The aim is to present some of the most prescribed premedication schemes prior to an upcoming dental analgesia in non-allergic patients. These schemes we would like to be proved as "standard protocols" in dental practice.